Metacognitive Assesment Profile of Prospective Chemistry Educators - Sumila, Sumila; Sahputra, Rachmat; Erlina, Erlina; Enawaty, Eny; Sasri, Risya (Jurnal Tadris Kimiya, 2023)
Metacognitive awareness (MA) plays an important role in classroom learning as it enhances self-teaching capabilities on students. Therefore, it is necessary to know the level of awareness possessed by a teacher. This study aimed to describe metacognitive awareness profile of prospective chemistry educators. The method of research is descriptive quantitative using survey methods. The participants consisted of students undergoing their final semester. The instrument used was the MAIT-18 (Metacognitive-Awareness Inventory for Teachers-18). This instrument has two indicators, specifically cognitive knowledge and regulation. The results showed that students had a good level of cognitive knowledge and regulation with 80% and 77%, respectively. Therefore, the overall percentage of metacognitive awareness obtained was 80%. These results suggest that prospective chemistry educators have a good awareness of metacognition. This is indicates they can influence positive things on students, foster autonomy in teaching and learning, also can be an asset to be an effective teacher.